Titanium alloy material micro-arc oxidation liquid and surface process thereof
By adding manganese dihydrogen phosphate to the acid microarc oxidation liquid, a dense ceramic oxide film layer is solved, and the problems of low surface hardness and poor corrosion resistance of titanium alloy materials are significantly improved, and its wear resistance and high-temperature oxidation resistance are achieved. Efficient surface modification.
Patent Information
- Application Number
- CN202411448073.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
AI Technical Summary
Titanium alloy materials have low surface hardness, poor wear resistance, and poor corrosion resistance in high-temperature environments and corrosive media, limiting their application range.
Manganese phosphate is added to the acidic microarc oxidation liquid, and a dense ceramic oxide film layer is generated through microarc oxidation technology, which improves the density and bonding strength of the film layer, and enhances wear resistance, heat oxidation and corrosion resistance.
The density and corrosion resistance of the microarc oxide film layer are significantly improved, the wear resistance and high-temperature oxidation resistance of titanium alloy materials are enhanced, and the process efficiency is high and the environmental pollution is low.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, relates to the surface treatment of titanium alloy materials, and in particular to a method for preparing a dense micro-arc oxidation film layer of titanium alloy materials through micro-arc oxidation. Background Art
[0002] Titanium alloy is an alloy composed of titanium and other elements. Titanium has two isomorphous crystals: titanium is an allotrope with a melting point of 1668℃. When it is below 882℃, it presents a close-packed hexagonal lattice structure, called α-titanium; when it is above 882℃, it presents a body-centered cubic lattice structure, called β-titanium. By taking advantage of the different characteristics of the above two structures of titanium, appropriate alloying elements are added to gradually change its phase transition temperature and component content to obtain titanium alloys with different structures.
[0003] Due to the low surface hardness of titanium alloy, it exhibits poor wear resistance when friction occurs on the surface. In addition, the contact between the friction pairs may also cause adhesive wear, abrasive wear and fatigue shedding. In particular, some shafts and aviation components may also suffer from micro-motion wear. and micro-disturbance wear. In addition, although a stable oxide film is easily formed on the surface of titanium alloy in the natural environment, in a long-term high-temperature environment, the thin oxide film reduces the bonding strength, resulting in reduced high-temperature oxidation resistance. In addition, titanium alloys will undergo comprehensive corrosion in reducing acids such as hydrochloric acid, sulfuric acid, phosphoric acid and hydrofluoric acid, and crevice corrosion will occur in aqueous solutions with chloride ions.
[0004] Therefore, different surface treatment technologies can improve the wear resistance, high temperature oxidation resistance, surface hardness and corrosion resistance of titanium alloy in reducing acid, thus broadening its application range. At present, there are roughly three types of titanium alloy surface treatment technologies: one is traditional surface treatment; the second is laser treatment and ion nitriding treatment; the third is anodizing and micro-arc oxidation treatment.
[0005] Traditional surface treatment methods include thermal diffusion, coating and deposition. Surface thermal diffusion mainly uses some powders, such as carbon powder and boron powder, to form a compound film layer on the surface of the sample. Although the obtained film layer has high bonding strength and fewer defects, it has high requirements for operating technology and environment. Surface coating often uses sol-gel technology, which generates a unique network structure through hydrolysis reaction and gel polymerization, which is coated on the surface to generate a nanostructure layer. Although sol-gel technology has low cost and little environmental pollution, its process is complicated and time-consuming. Surface deposition technology uses physical and chemical methods to make titanium alloy react with gas atmosphere. The film layer generated by surface deposition has good density, but the reaction temperature requirement is high and impurities are easily generated in the film layer.
[0006] Plasma nitriding technology is a process in which titanium alloy forms an atmosphere with ion nitrogen through the ion glow generated by the breakdown of the cathode and anode in low pressure, and then forms an oxide film through a series of reaction penetrations. Although the performance of the film layer is improved, the nitriding layer is shallow and there are many factors affecting the technology, such as time, voltage, temperature, etc. Surface laser treatment technology is divided into direct energy deposition coating and laser powder alloying. Direct energy deposition coating uses the energy of the laser beam to melt the metal wire or metal powder and then form a film, while laser powder alloying is to pre-lay metal powder that meets the performance of the film layer, and then the laser moves back and forth to form a film. These two The film layer prepared by the method generates stress due to the rapid change of internal temperature, which leads to problems such as cracks, shedding and poor bonding strength of the film layer.
[0007] The anodic oxidation of titanium alloy is a process in which electrochemical oxidation occurs on the surface of the film layer and then an oxide film is formed. The electrochemical reaction process of anodic oxidation is: Ti→Ti 2+ →Ti 4+ →TiO2. Anodization is mostly used for the preparation of thin films. The film's super strong moisture sensitivity, gas sensitivity and photocatalytic properties are used in many sensor elements. In addition, anodization can also prepare TiO2 nanotubes in electrolytes containing fluoride ions, which are mostly used in the medical field. Although anodization has many advantages, its operating voltage is generally in the low voltage area. At the same time, most electrolytes use acidic electrolytes, which are more polluting to the environment. In addition, the pretreatment process is relatively cumbersome, and the film thickness is relatively small.
[0008] The micro-arc oxidation technology is developed on the basis of anodizing. It breaks through the limitation of Faraday's working voltage and introduces the voltage into the high voltage area. Under the action of high voltage and strong electric field plasma, a series of physical and chemical reactions occur, including: anodizing, spark discharge, micro-arc oxidation, and arc extinction. As the surface discharge occurs, the surface film layer also grows rapidly, and the formation of the film layer greatly improves the performance of the titanium alloy substrate.
[0009] Micro-arc oxidation (MAO) is also known as micro-plasma oxidation (MPO) or anodic spark deposition (ASD). This technology places valve metals such as Al, Mg, Ti, Zr or their alloys in an aqueous electrolyte solution, and uses the instantaneous high-temperature sintering effect of the micro-arc area to directly form a crystalline oxide ceramic phase structure film layer that is metallurgically bonded to the substrate on the surface of the valve metal or its alloy.
[0010] In the early stage of micro-arc oxidation, an acidic system is often used. Wang Jianmin et al. found that compared with 10% H3PO4 electrolyte, the arc starting voltage of 10% H2SO4 electrolyte was lower, the pore size of the film was reduced, and the film showed a porous structure. Guan Xin et al. found that the main phases of the oxide film prepared in H2SO4 were anatase and rutile phases, while the main phase of the oxide film prepared in H3PO4 was amorphous titanium oxide phase. Summary of the invention
[0011] Based on the above content, the present invention has discovered for the first time that adding manganese dihydrogen phosphate to the acidic micro-arc oxidation solution can significantly improve the structure of the micro-arc oxidation film layer, significantly improve the pore size and density of the micro-arc oxidation film layer, especially improve the void structure of the dense layer therein, so that the micro-arc oxidation film layer has a high bonding strength with the substrate and is not easy to fall off. The micro-arc oxidation film has extremely high wear resistance, thermal oxidation resistance, and corrosion resistance. In addition, since the film layer is a ceramic film layer, the film layer has good insulation properties, the efficiency of micro-arc oxidation sample preparation is high, and the environmental pollution is small.
[0012] Specifically, the present invention provides a titanium alloy material surface process, comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature.
[0013] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0014] It should be noted that the micro-arc oxidation liquid of the present invention can be weakly acidic or acidic, but cannot be alkaline.
[0015] The micro-arc oxidation solution contains 8-9g / L manganese dihydrogen phosphate.
[0016] The micro-arc oxidation solution is composed of 20-25 g / L sulfuric acid, 10-12 g / L manganese dihydrogen phosphate, 4-5 g / L boric acid, 1-2 g / L potassium tartrate and deionized water.
[0017] The thickness of the micro-arc oxidation on the titanium alloy surface is 30-80 μm.
[0018] The addition of manganese dihydrogen phosphate in the present invention increases the energy carried by plasma during breakdown during micro-arc oxidation. Under the action of high temperature and high pressure in the discharge channel, a large amount of molten oxide participating in film formation accumulates around the micropores and continuously diffuses to the surroundings. While diffusing, the molten oxide solidifies and covers some micropores due to the extremely cold effect of the electrolyte. The diffusion of the molten oxide covers these micropores, and the manganese element diffuses inward to cover the holes of the dense layer and remains at the bottom of the film layer, thereby significantly reducing the porosity in the dense layer. While the cross section of the film layer becomes dense, the fluctuation trend of the cross section of the film layer begins to increase, the large-sized through holes and the holes distributed longitudinally and transversely inside the film layer decrease, and the thickness of the film layer also begins to increase, thereby obtaining a dense and corrosion-resistant micro-arc oxidation film layer.
[0019] In addition, micro-arc oxidation is affected by multiple factors, among which electrical parameters are an important factor. Electrical parameters include: power mode, voltage, frequency and duty cycle.
[0020] Different power supply types will have different power supply modes, which will affect the output form of voltage. The first power supply used was DC power supply. Due to its high power consumption, it was only suitable for thin film preparation and parts with simple configurations, and was gradually eliminated. Later, AC power supply appeared. The film layer prepared by the constant voltage mode of AC power supply improved the structure of the film layer, but the output accuracy was low and the adjustable range was relatively narrow. With the continuous improvement of power supply, unipolar pulse power supply and bipolar pulse power supply appeared. Compared with DC power supply and AC power supply, they have a wide adjustable range and are easy to control, and the corrosion resistance of the film layer prepared by bipolar pulse power supply is better than that of unipolar pulse power supply.
[0021] During the micro-arc oxidation process, the magnitude of the voltage determines the strength of the film breakdown discharge and plays a vital role. As the voltage gradually increases, the growth rate of the titanium alloy film increases, and the corrosion resistance of the film is also significantly enhanced, which is also conducive to the transformation of metastable anatase to stable rutile. The film of the present invention has almost no cracks. However, too high a voltage will increase the micropore diameter of the film, increase the surface roughness of the film, and reduce the corrosion resistance of the film. Therefore, when micro-arc oxidation is performed on different titanium metals, a reasonable voltage can produce a film with excellent performance.
[0022] The duty cycle is the ratio of the arcing duration in a pulse cycle to the total duration. The duty cycle is proportional to the energy of a single pulse. As the duty cycle increases, the content of rutile TiO2 in the film increases, and the film growth rate, the number of micropores and the film thickness show a trend of first increasing and then decreasing. However, a duty cycle that is too high will cause defects in the film and produce microcracks, thereby reducing the corrosion resistance of the film. Therefore, too high or too low a frequency and duty cycle will not necessarily produce a film with excellent performance. A reasonable range should be selected and considered comprehensively.
[0023] Time and temperature are another important factor affecting micro-arc oxidation, and they also have different effects on the performance of the film. For example, as the micro-arc oxidation time increases, the micropore diameter increases, while the number of micropores begins to decrease, and the roughness of the film surface is also affected. For example, as the solution temperature gradually increases, the arc starting voltage decreases, while the film roughness and micropore diameter increase. When the solution temperature rises to 40°C, the micropore diameter of the film decreases, the overlap between micropores increases, and the film becomes smooth with fewer cracks.
[0024] Beneficial technical effects: The present invention has discovered for the first time that adding manganese dihydrogen phosphate to an acidic micro-arc oxidation solution can significantly improve the structure of the micro-arc oxidation film layer, significantly improve the pore size and density of the micro-arc oxidation film layer, especially improve the void structure of the dense layer therein, so that the micro-arc oxidation film layer has a high bonding strength with the substrate and is not easy to fall off. The micro-arc oxidation film has extremely high wear resistance, thermal oxidation resistance, and corrosion resistance. In addition, since the film layer is a ceramic film layer, the film layer has good insulation properties, the efficiency of micro-arc oxidation sample preparation is high, and the environmental pollution is small.
[0025] Beneficial technical effects: The present invention adds manganese dihydrogen phosphate to the acidic micro-arc oxidation solution to significantly improve the structure of the micro-arc oxidation film layer, significantly improve the porosity, density and roughness of the micro-arc oxidation film layer, especially improve the void structure of the dense layer therein, so that the micro-arc oxidation film layer has a high bonding strength with the substrate and is not easy to fall off. The micro-arc oxidation film has extremely high wear resistance, thermal oxidation resistance, and corrosion resistance. In addition, since the film layer is a ceramic film layer, the film layer has good insulation properties, the efficiency of micro-arc oxidation sample preparation is high, and the environmental pollution is small. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Attached Figure 1 Cross-sectional view and partial enlarged view of the micro-arc oxidation product of Example 1 of the present invention.
[0027] Attached Figure 2 Cross-sectional view and partial enlarged view of the micro-arc oxidation product of Comparative Example 1 of the present invention.
[0028] Attached Figure 3 Corrosion resistance test results of the embodiments of the present invention and the comparative examples.
[0029] Attached Figure 4 The film layer morphology images of Comparative Example 1, Comparative Example 3 and Example 2 of the present invention. DETAILED DESCRIPTION Example 1
[0030] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 440 V, negative voltage 100 V, frequency 340 Hz; positive duty cycle 50%, negative duty cycle 20%, time 18 min, and the initial electrolyte temperature is room temperature.
[0031] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0032] The micro-arc oxidation solution consists of 20 g / L sulfuric acid, 10 g / L manganese dihydrogen phosphate, 4 g / L boric acid, 1 g / L potassium tartrate and deionized water. Example 2
[0033] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature.
[0034] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0035] The micro-arc oxidation solution consists of 22.5 g / L sulfuric acid, 11 g / L manganese dihydrogen phosphate, 4.5 g / L boric acid, 1.5 g / L potassium tartrate and deionized water. Example 3
[0036] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 460 V, negative voltage 120 V, frequency 360 Hz; positive duty cycle 60%, negative duty cycle 30%, time 22 min, and the initial electrolyte temperature is room temperature.
[0037] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0038] The micro-arc oxidation solution consists of 25 g / L sulfuric acid, 12 g / L manganese dihydrogen phosphate, 5 g / L boric acid, 2 g / L potassium tartrate and deionized water.
[0039] Comparative example 1.
[0040] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature.
[0041] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0042] The micro-arc oxidation solution consists of 22.5 g / L sulfuric acid, 11 g / L manganese sulfate, 4.5 g / L boric acid, 1.5 g / L potassium tartrate and deionized water.
[0043] Comparative Example 2.
[0044] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature.
[0045] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0046] The micro-arc oxidation solution consists of 22.5 g / L sulfuric acid, 11 g / L potassium permanganate, 4.5 g / L boric acid, 1.5 g / L potassium tartrate and deionized water.
[0047] Comparative Example 3.
[0048] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are: voltage 450 V, time 20 min, and initial electrolyte temperature is room temperature.
[0049] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0050] The micro-arc oxidation solution consists of 22.5 g / L sulfuric acid, 11 g / L manganese phosphate, 4.5 g / L boric acid, 1.5 g / L potassium tartrate and deionized water.
[0051] Comparative example 4.
[0052] A titanium alloy material surface process, characterized by comprising the following steps: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature.
[0053] (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
[0054] The micro-arc oxidation solution consists of 22.5 g / L sulfuric acid, 11 g / L manganese phosphate, 4.5 g / L boric acid, 1.5 g / L potassium tartrate and deionized water.
[0055] First, under the premise that the main difference between Comparative Example 1 and Example 2 is the addition of different manganese, see the attached Figure 1 and attached Figure 2 From the partial enlarged view of the black dotted line position in FIG. 1 (this part is the junction of the substrate and the micro-arc oxidation layer, i.e., the dense layer), it can be seen that the micro-arc oxidation film layer added with manganese dihydrogen phosphate in the micro-arc oxidation solution of the present invention is more dense, especially the effect on the dense layer is more obvious, see the attached Figure 4From the film layer diagrams of Comparative Example 1 and Example 2, it can be seen that not only the dense layer has a significant impact, but also the porosity of the surface morphology has a significant impact. See attached Figure 3 The corrosion resistance test of the embodiments and comparative examples was carried out, wherein the corrosion potential Ecorr of comparative example 1, comparative example 2, comparative example 3, comparative example 4, and embodiment 2 were -0.287 V, -0.196 V, -0.175 V, -0.076 V, and -0.018 V, respectively; the corrosion current density Icorr of comparative example 1, comparative example 2, comparative example 3, comparative example 4, and embodiment 2 were 2.10*10 -6 A / cm 2 , 1.03*10 -6 A / cm 2 ,3.14*10 -7 A / cm 2 ,9.20*10 -8 A / cm 2 ,1.94*10 -8 A / cm 2 ,From the above results, it can be seen that the two key factors for ,corrosion resistance are manganese compounds and voltage conditions, among which ,manganese phosphate dihydrogen and manganese phosphate show better ,smaller porosity, and bidirectional voltage is better than ordinary voltage.
[0056] In addition, see Appendix Figure 4 The porosities of the surface film layers of Comparative Example 1, Comparative Example 3 and Example 2 were 9.1%, 6.5% and 4.9%, respectively, and the corresponding surface roughness Ra were 2.538 μm, 1.989 μm and 1.889 μm, respectively. That is, the micro-arc oxidation film prepared in Example 2 showed the lowest porosity and roughness.
[0057] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A titanium alloy material surface process, characterized in that The steps include: (1) Grind the titanium alloy on 80#, 180#, 400#, 800#, and 1200# sandpaper in sequence; (2) Rinse with deionized water, ultrasonic clean with ethanol, and dry with cold air; (3) The titanium alloy treated in step (2) is used as an anode and immersed in a micro-arc oxidation solution for micro-arc oxidation. The electrolysis parameters of the micro-arc oxidation are as follows: forward voltage 450 V, negative voltage 110 V, frequency 350 Hz; positive duty cycle 55%, negative duty cycle 25%, time 20 min, and the initial electrolyte temperature is room temperature; (4) The titanium alloy-based micro-arc oxidation material is obtained by washing with deionized water and anhydrous ethanol in turn and drying.
2. A titanium alloy material surface process as claimed in claim 1, characterized in that The micro-arc oxidation liquid is acidic.
3. A titanium alloy material surface process as claimed in claim 1, characterized in that The micro-arc oxidation solution contains 8-9g / L manganese dihydrogen phosphate.
4. A titanium alloy material surface process as claimed in claim 1, characterized in that The micro-arc oxidation solution is composed of 20-25 g / L sulfuric acid, 10-12 g / L manganese dihydrogen phosphate, 4-5 g / L boric acid, 1-2 g / L potassium tartrate and deionized water.
5. The titanium alloy surface process according to claim 1, characterized in that The thickness of the micro-arc oxidation on the titanium alloy surface is 30-80 μm.
6. A titanium alloy material surface process as claimed in claim 1, characterized in that The titanium alloy material should include pure titanium.
